Functional Analysis of Phagocyte Activity in Whole Blood from HIV/Tuberculosis-Infected Individuals Using a Novel Flow Cytometry-Based Assay - Gupta-Wright, Ankur; Tembo, Dumizulu; Jambo, Kondwani C.; Chimbayo, Elizabeth; Mvaya, Leonard; Caldwell, Shannon; Russell, David G.; Mwandumba, Henry C. (Frontiers in Immunology, 2017)
The accurate assessment of immune competence through ex vivo analysis is paramount to our understanding of those immune mechanisms that lead to protection or susceptibility against a broad range of human pathogens. We have developed a flow cytometry-based, whole blood phagocyte functional assay that utilizes the inflammatory inducer zymosan, coupled to Oxyburst SE, a fluorescent reporter of phagosomal oxidase activity. The assay measures both phagocytic uptake and the superoxide burst in the phagocyte populations in whole blood. We utilized this assay to demonstrate impaired superoxide burst activity in the phagocytes of hospitalised HIV-positive patients with laboratory confirmed tuberculosis. These data validate the use of the assay to assess the immune competence of patients in a clinical setting. The method is highly reproducible with minimal intra-individual variation and opens opportunities for the rapid assessment of cellular immune competence in peripheral blood in a disease setting.